HUBUNGAN KELENTURAN PERGELANGAN TANGAN, KOORDINASI MATA DAN TANGAN DENGAN KETEPATAN PUKULAN BACKHAND DALAM PERMAINAN TENIS MEJA ATLET PUTRA CLUB MALAY SPORT PEKANBARU - Syafriwan, Dio; Slamet, Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem of this research is that there are still many athletes who are less able to take advantage of the flexibility of the wrist when athletes do backhand techniques. Coordination of the Eyes and Hands of the athlete has not been maximized so that the results of the punch are not optimal. The purpose of this study was to determine the Correlation of Wrist Flexibility, Eye and Hand Coordination with the Accuracy of Backhand Punch in the Table Tennis Games for Male Athlete Club Malay Sport Pekanbaru. This research belongs to the type of correlational research. This study began after obtaining approval from supervisors and examiners to retrieve data in the field, namely in May 2019 to November 2019. The population of this research is the Pekanbaru Malay Sports Club Putra Athletes, amounting to 12 people. The sampling technique used is total sampling. Based on the analysis of the data obtained by the correlation coefficient of r = 0.831 where the significance was tested by the F-test and obtained a fcount of 7.82, meaning tcount (7.82)> ttable (4.74) thus Ha was accepted. In other words there is a significant relationship between wrist flexion (X1) and eye and hand coordination (X2) on the accuracy of the backhand stroke (Y).Key Words: Determination, Coordination, Accuracy